CHALLENGES IN TRANSLATING PHRASEOLOGICAL UNITS FROM CLASSICAL UZBEK TEXTS INTO MODERN UZBEK AND ENGLISH - Shukurova Zilola Fazlidinovna (Bright Mind Publishing, 2025)
This research explores the translation of phraseological units (PUs) from classical texts into both modern Uzbek (tabdil) and English, highlighting the translator's ability to retain the original meaning and cultural nuances. This article explores the development and translation of Uzbek phraseological units, emphasizing the contributions of key scholars in the field such as Sh. Rahmatullayev, Z. Teshaboyeva and others. The study examines the theoretical and practical aspects of phraseology, with a focus on how idiomatic expressions are formed and their cultural significance in both the original and translated texts. Through the analysis of classical works, particularly the Tarixi Rashidiy, the paper addresses the complexities of translating phraseological units (PUs) from classical Uzbek texts into English and modern Uzbek. It highlights the challenges in maintaining the literal meaning of idiomatic expressions while preserving their cultural and philosophical nuances. The research also underscores the importance of context and interpretive adaptation when dealing with historical or religious expressions that do not have direct equivalents in the target language. By examining the works of renowned scholars and translators, the article contributes to the understanding of phraseological translation, offering insights into how idiomatic expressions reflect both linguistic and cultural worldviews.
Keywords: Phraseology, fixed expressions, analysis, classical Uzbek literature, translation studies, semantic equivalence, linguistic adaptation, historical texts, verbal phraseological units.